What Are We to Do with the Foundation of Hebrews 6:1-2? - Davies, John A. (Reformed theological review, 2024)
A longstanding puzzle in Heb 6:1-2 has been why the author seems to downplay such fundamental teachings as faith in God, repentance, resurrection, and judgement. There has often been an assumed or stated identification of the ‘account of the beginning of the Messiah’, which is to be left behind, and the itemised fundamental tenets. This article challenges this identification and sees the ‘account of the beginning of the Messiah’ as the Old Testament, particularly its account of the rituals that spoke of the work of the Messiah, and which is to be abandoned, while the foundational tenets that have their origin in the old covenant era continue and do not need to be established de novo under the new covenant.